Which are the best VO2 sampling intervals to characterize low to severe swimming intensities? - de Jesus, K.; Guidetti, L.; de Jesus, K.; Vilas-Boas, J. P.; Baldari, C.; Fernandes, R. J. (International Journal of Sports Medicine, 2014)
Cardiorespiratory response in swimming has been used to better understand aerobic performance, especially by assessing oxygen uptake (VO2). The current study aimed to compare different VO2 time-averaging intervals throughout low to severe swimming intensities, hypothesizing that VO2 values are similar for different time averages at low to moderate and heavy swimming intensities, but not for the severe domain. 20 male trained swimmers completed an incremental protocol of 7×200 m until exhaustion (0.05 m/s increments and 30 s intervals). VO2 was measured by a portable gas analyser connected to a snorkel system. 6 time average intervals (breath-by-breath, 5, 10, 15, 20 and 30 s) were compared for all the protocol steps. Breath-by-breath and 5 s average exhibited higher VO2 values than averages=10s for all swimming intensities (P=0.02; partial 2=0.28). VO2 values did not differ between 10, 15, 20 and 30?s averages throughout the incremental protocol (P>0.05; partial 2=0.05). Furthermore, 10 and 15 s averages showed the lowest VO2 mean difference (0.19mL·kg-1·min-1). For the 6 time average intervals analysed, 10 and 15 s averages were those that showed the lowest changes on VO2 values. We recommended the use of 10 and 15 s time averaging intervals to determine relevant respiratory gas exchange parameters along a large spectrum of swimming intensities.